2006
DOI: 10.1002/jssc.200500483
|View full text |Cite
|
Sign up to set email alerts
|

Rapid separation of four main taxoids in Taxus species by a combined LLP‐SPE‐HPLC (PAD) procedure

Abstract: A method is described for the simultaneous determination of paclitaxel and three related taxoids, 10-deacetylbaccatin III (10-DAB III), baccatin III, and cephalomannine, in the extracts from the needles of three Chinese yew species, Taxus cuspidata, T. chinensis, and T. media. SPE was applied as the sample preparation technique and RP-HPLC with a photodiode array detector (PAD) was used for the analysis of extract samples. The crude extracts were treated with an improved SPE cartridge packed with a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
2
18
1
Order By: Relevance
“…However, the contents of other taxoids such as 10-DAB III and 7-xyl-10-DAT are much higher than paclitaxel in Taxus species, and pharmacological experiments have indicated that some of them, such as 7-xyl-10-DAT, exert strong anti-tumor activity (Lataste et al, 1984). These taxoids are precursors necessary for the biosynthesis of paclitaxel in the plants (Madhusudanan et al, 2002b;Zu et al, 2006;Ballero et al, 2003;Mroczek and Glowniak, 2001). Therefore, these taxoids have become one of the hot spots in the field of paclitaxel research in recent years.…”
Section: Simultaneous Determination Of Main Taxoids Inmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the contents of other taxoids such as 10-DAB III and 7-xyl-10-DAT are much higher than paclitaxel in Taxus species, and pharmacological experiments have indicated that some of them, such as 7-xyl-10-DAT, exert strong anti-tumor activity (Lataste et al, 1984). These taxoids are precursors necessary for the biosynthesis of paclitaxel in the plants (Madhusudanan et al, 2002b;Zu et al, 2006;Ballero et al, 2003;Mroczek and Glowniak, 2001). Therefore, these taxoids have become one of the hot spots in the field of paclitaxel research in recent years.…”
Section: Simultaneous Determination Of Main Taxoids Inmentioning
confidence: 99%
“…Solid-phase extraction (SPE) made the determination and preparation stage faster, easier, and more automatable (Son et al, 2000). There are many reports on SPE of taxoids on C 18 sorbent (Mattina and MacEachen, 1994;Glowniak et al, 1996), cyano bonded silica phases (Sparreboom et al, 1995;Huizing et al, 1995), and 1-vinyl-pyrrolidin-2-one and divinyl-benzene (Waters Oasis HLB) sorbent (Zu et al, 2006). Octadecyl-bonded SPE was reported to obtain five taxanes in needle extracts using a PFP column (Mattina and MacEachen, 1994).…”
Section: Simultaneous Determination Of Main Taxoids Inmentioning
confidence: 99%
“…It is regarded as one of the most useful anticancer drugs of plant origin available today. It is effective in the treatment of many tumor types, such as ovarian, breast, melanoma, head, neck, bladder, gastrointestinal, lung cancer, and non-small-cell lung cancer [1][2][3], as well as for AIDS-related Kaposi's sarcoma [4][5][6]. Its fundamental anticancer mechanism is unique [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, no superparamagnetic MIP was reported. In this 3 work, the molecularly imprinted particles with a superparamagnetic Fe 3 O 4 @SiO 2 core (Fe 3 O 4 @SiO 2 @MIP) for rapid, selective, simultaneous enrichment and separation of four taxoids in the extracts of T. × Media were synthesized by a multi-step procedure illustrated in Fig. 2 [19].…”
Section: Mediamentioning
confidence: 99%
“…Besides paclitaxel numerous related taxoids have been identified in the twigs of T. × media, including 10-deacetylbaccatin III (10-DAB), baccatin III, and cephalomannine ( Fig. 1) [2,3]. Cephalomannine also has important bioactivity [4].…”
Section: Introductionmentioning
confidence: 99%